Type I Protein C Deficiency in French Canadians: Evidence of a Founder Effect and Association of Specific Protein C Gene Mutations with Plasma Protein C Levels - Couture, Patrick; Demers, Christine; Morissette, Jean; Delage, Robert; Jomphe, Michèle; Couture, Louis; Simard, Jacques (Thrombosis and Haemostasis, 1998)
Protein C (PROC) deficiency is one of the most common autosomal codominant diseases. Although more than 150 germline mutations in the PROC gene have been described around the world, the spectrum of mutations among French Canadians is unknown. We have identified one frameshift (3363 ins C) and two missense mutations (R178Q and T298M) in 7 French Canadian families with type I PROC deficiency. In order to demonstrate a possible founder effect for the 3363 ins C mutation, we have constructed a high-resolution genetic map to locate several highly polymorphic markers close to PROC locus. We have then genotyped five markers in 36 heterozygotes for the 3363 ins C mutation. Our data suggest that these patients carry a common haplotype at the PROC locus. Immunologic plasma PROC levels of heterozygotes and genetically normal relatives were also correlated with the nature of the mutation in the coding sequence and with the genotype of three polymorphisms in the PROC promoter. We found that the mean immunologic plasma PROC levels were lower in heterozygotes for the frameshift mutation 3363 ins C compared to heterozygotes for one of the two missense mutations R178Q and T298M (0.46 vs 0.61; P = 0.0004). Moreover, this difference cannot be explained by the genetic variation of the three polymorphisms in the PROC promoter which accounts for only 10.4% of the variation of immunologic PROC levels in non-deficient subjects. These results suggest that the nature of the mutation in the coding sequence of PROC gene may modulate immunologic plasma PROC levels.